Global diversity and phylogeny of the Phellinus igniarius complex (Hymenochaetales, Basidiomycota) with the description of five new species - Zhou, Li-Wei; Vlasák, Josef; Qin, Wen-Min; Dai, Yu-Cheng (Mycologia, 2015)
The Phellinus igniarius complex corresponds to Phellinus s.s., a well supported clade in the polyphyletic Phellinus s.l. studied worldwide. Recently a molecular phylogeny of this complex was performed for the European and North American species. In this study we expand the taxon samplings of the P. igniarius complex to include 59, seven and 12 additional collections originating from China, Czech Republic and USA, respectively. We generated 78 nuc rDNA ITS1-5.8S-ITS2 (ITS) and 42 translation elongation factor 1-α gene (tef1α) sequences. Based on the morphological and phylogenetic (combined ITS and tef1α dataset) analyses, Phellinus monticola, P. orientoasiaticus, P. padicola, P. parmastoi and P. pomaceoides are newly described and illustrated from China and USA. Phellinus pseudoigniarius is treated as a later synonym of P. igniarius, whereas Phellinus betulinus subsp. betulinus is accepted as P. betulinus. A total of 15 species are accepted in the P. igniarius complex worldwide. Of them, 10 species are distributed in eastern Asia, eight in Europe and six in North America. The taxonomy, phylogeny, host associations and geographic distributions of these 15 species are briefly discussed.
Keywords: Dálný východ; Base Sequence; ribozomální DNA; Europe; DNA, Ribosomal; plodnice hub; Fruiting Bodies, Fungal; Molecular Sequence Data; Evropa; DNA, Fungal; mezerníky ribozomální DNA; Genetic Variation; Phylogeny; Asia, Eastern; molekulární sekvence - údaje; North America; Severní Amerika; sekvence nukleotidů; Spores, Fungal; Sequence Analysis, DNA; DNA fungální; DNA, Ribosomal Spacer; sekvenční analýza DNA; fylogeneze; spory hub; genetická variace; Basidiomycota